(untitled) (Fiep Bulletin - online, 2012)
The aim of this study is to verify the body image perception in male undergraduate students who practice strength-training and the relationship of it with the data acquired from the antropometric evaluation. The sample was composed of 37 male undergraduate students who practice strength-training at the age of 17 to 25 years old. The data collecting was carried out at a strength-training gym at Maringá – PR. We assessed the antropometric measures: weight, height and skin folds thickness in order to determine the fat percentage and BMI. At the final antropometric data collecting stage we applied the BSQ, Body Shape Questionnaire, adapted to male strength-training practitioners. We concluded that male youngsters do not present body self-image distortion, which can be associated to the antropometric variables indicating that the individuals are usually in eutrophy.